Comparative Study for the Effect of Fixative Material Type and Perfume Formulation Parameters on the Fixation time of Local Formulated Perfume with Brand Perfumes - Alaa D. Jawad Al-Bayati (Engineering and Technology Journal, 2016)
The effect of type of fixative material and the perfume formulation parameters (Concentration of ethyl alcohol, percentage of perfume and the percentage of the fixative used) were studied to determine the optimum conditions give perfume with high retention time (fixative), also the fixation time was compared with brand perfumes. Four fixative materials were studied; Sandal oil, Musk oil, Glycerin and benzyl benzoate. Design of experiments (DOE) with Minitab 15 software was done and leaded to minimum 20 runs necessary for this study. For the four fixatives the runs were eighty .The maximum fixation time of all the fixation materials are 6.3, 6.1, 5.9 and 5.9 h/g for Glycerin, Musk, Sandalwood and benzyl benzoate respectively with formulation parameters of (75% alcohol concentration, 30% perfume addition and 0.1% fixative material) for Musk, Glycerin and benzyl benzoate fixative materials and (85% alcohol concentration, 17.5% perfume addition and 0.55% fixative material) for Sandalwood as fixative material. The brand perfumes as Channel give 2h/g fixation time and for many other brand perfumes give fixation time in the range of 2.2-2.9h/g.